Reaping pest-free ber - Haldhar, Shravan M; Kumar, Kamlesh (Indian Horticulture, 2019)
Ber is an important fruit crop for arid and semi-arid region and an extremely drought hardy and native fruit of India. At present, 130 species of insect-pests have been recorded in India but only few species have attained the pest status and cause substantial economic damage to ber. Out of these, 3 insects species, viz. fruit fly, Carpomyia vesuviana, fruit borer, Meridarchis scyrodes and stone weevil, Aubeus himalayanus were recorded as major pests. Whereas two insects species, viz. butter fly, Tarucus theophrastus and thrips, Scirtothrips dorsalis were recorded as moderate pests. As many as 7 insect species, viz. Myllocerus dentifer, M. blandus, Amblyrrhinus poricollis, Synclera univocolis, Larvacarus transitans, Indarbela sp. and Odontotermes sp. were recorded as minor pests. For managing them, some simple management (IPM) tactics that keep away the insect-pests and alleviate the chemical methods are recommended.